ROLE OF TUMOUR NECROSIS FACTOR IN PATHOGENESIS OF RADICULAR CYST - Qureshi, Waqar -ur-Rehman; Idris, Muhammad; Khan, Shahbaz Ali (Journal of Ayub Medical College Abbottabad, 2011)
Background: The radicular cyst is very common odontogenic cyst of the jaws, which is usually associated with a tooth with necrotic pulp. The cyst formation requires proliferation of the epithelial rest cells of Malassez present in the periodontal ligament. . Proliferation of epithelial rest cells of Malassez is an essential event in the Pathogenesis of radicular cyst. The wall of the cyst contains epithelial cells, macrophages, fibroblasts and other cells. TNF is one of inflammatory mediators, which is produced by macrophages and monocytes. This study was carried out to investigate the role of tumour necrosis factor in the pathogenesis of radicular cyst, which is by far the commonest cystic lesion of the jaws. Methods: Explants from 20 radicular cysts were cultured in vitro to grow the epithelial cells. However, the cultures were rapidly contaminated with fibroblasts and it was impossible to grow the epithelial cells separately. Therefore, the proliferative effect of Tumour Necrosis Factor (TNF) was studied on mammalian epithelial cells. Results: TNF at low concentration had a proliferative effect on the epithelial cells, which may play some role in pathogenesis of radicular cyst. Conclusion: TNF stimulated the epithelial cell proliferation in low concentration and inhibit the proliferation in higher concentrations. These two effects may have some implications in the pathogenesis of radicular cyst. Keywords: Tumour necrosis factor, epithelial rest cells of Malassez, macrophages and radicular cyst